2015
DOI: 10.1038/srep17391
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of novel inhibitors of the sodium-coupled citrate transporter (NaCT or SLC13A5)

Abstract: Citrate is a key regulatory metabolic intermediate as it facilitates the integration of the glycolysis and lipid synthesis pathways. Inhibition of hepatic extracellular citrate uptake, by blocking the sodium-coupled citrate transporter (NaCT or SLC13A5), has been suggested as a potential therapeutic approach to treat metabolic disorders. NaCT transports citrate from the blood into the cell coupled to the transport of sodium ions. The studies herein report the identification and characterization of a novel smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(143 citation statements)
references
References 47 publications
7
134
0
2
Order By: Relevance
“…Interestingly, heterozygotes may have some benefit relating to reduced liver citrate transport. A current focus in diabetes drug development targets the liver NaCT with small molecule inhibitors that do not penetrate the CNS (11,12). There is some evidence from other members of the SLC13 family that dimer formation can alter function, both homodimers (19) and heterodimers with other proteins (42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, heterozygotes may have some benefit relating to reduced liver citrate transport. A current focus in diabetes drug development targets the liver NaCT with small molecule inhibitors that do not penetrate the CNS (11,12). There is some evidence from other members of the SLC13 family that dimer formation can alter function, both homodimers (19) and heterodimers with other proteins (42).…”
Section: Discussionmentioning
confidence: 99%
“…A total of six NaCT mutants were prepared: four point mutations identified in this study, Y82C, G219R, T227M and L492P (Table 1 and Figure 1), and one mutation, L488P, identified previously (2). In addition, we prepared the DelG mutant of hNaCT, with a nucleotide deletion of hepatocytes, NaCT expression is correlated with lipid accumulation and triglyceride synthesis (10,11). Furthermore, inhibition of NaCT-mediated citrate transport by the liver is emerging as a therapeutic approach for the treatment of metabolic disorders, such as diabetes (11,12).…”
Section: Expression Of Nact Mutants In Cos-7 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of hepatic extracellular citrate uptake through SLC13A5 has been suggested as a potential therapeutic approach to treat metabolic diseases (Huard et al, 2015(Huard et al, , 2016Li et al, 2016). The SLC13A family contains five family members: SLC13A1 and SLC13A4 mainly transport sulfate, and SLC13A2, SLC13A3, and SLC13A5 transport di-and tri-carboxylates such as citrate (Lee et al, 2005;Bergeron et al, 2013).…”
Section: Introductionmentioning
confidence: 99%